The effect of magnetic order in amorphous LaSrMnO films on an anomaly in the variable range hopping - Okunev, V.D.; Samoilenko, Z.A.; Pafomov, N.N.; Plehov, A.L.; Szymczak, R.; Szymczak, H.; Lewandowski, S.J. (Physics letters. A, 2009)
Anomalies of a variable range hopping (VRH) in amorphous LaSrMnO films containing ferromagnetic (FM) and antiferromagnetic (AFM) crystalline clusters are investigated. Anomalies are constituted, in the 190–130 K temperature interval, by an increase of the local activation energy ( ε a ) with decreasing temperature. It is established that the increase in ε a is caused by magnetic ordering of AFM clusters containing Mn 3+ and Mn 4+ centers participating in VRH.